Hepatic adenoma in a 7-year-old girl: a case report and literature review - Yan Gao; Jun Zhou; Yu-cheng Xie; Li-juan Qiu; Ling Duan; Zhi-xiang A; Hong-fang Wu; Meng-xing Lv (BMC, 2023)
Abstract Background Hepatocellular adenomas (HCAs) are rare benign tumors of the liver that occur predominantly in women taking oral contraceptives. In children, HCAs comprise < 5% of hepatic tumors. We report a case of HCAs in a 7-year-old girl with estrogen and glucose imbalance. Case presentation A 7-year-old girl was presented to our hospital with bilateral breast enlargement for 2 months, polydipsia, polyuria, polyphagia, hyperglycemia, and significant weight gain. Computed tomography (CT) showed a 7.2 cm×6.9 cm×5.3 cm round-shaped mass in the left inner lobe of the liver, ovarian ultrasound showed multiple follicles in the ovaries bilaterally, and cranial magnetic resonance imaging (MRI) showed an enlarged superior pituitary. Hematological and biochemical results were as follows: fasting glucose was 19.7 mmol/L, estradiol was 122.9 pmol/L, follicle-stimulating hormone 10.81 IU/L, luteinizing hormone 10.99 IU/L, insulin-like growth factor 1,513 ng/mL, glutamine aminotransferase 86 U/L, and alkaline phosphatase 362 U/L. Thyroid functions, methemoglobin, fetal protein, carcinoembryonic antigen, and chorionic gonadotropin were normal. The patient had a complete surgical resection of the liver tumor, and the postoperative histopathological diagnosis was HCAs. After the surgery, insulin was injected and the glucose levels were stable. During the 36-month follow-up period, neither tumor recurrence nor significant abnormalities were detected using color Doppler ultrasound of the liver. The child's precocious puberty is currently under control. Conclusions HCAs are particularly rare in children with liver tumors, and risk factors for the development of HCAs in children include sex hormone imbalance, obesity, Fanconi anemia (FA), glycogen storage diseases (GSDs) type I, III, and IV, galactosemia, immunodeficiency, congenital portosystemic shunts (CPSS), cardiac hepatopathy status-post Fontan procedure, Hurler syndrome, familial adenomatous polyposis, germline HNF1A mutations, and maturity-onset diabetes of the young type 3. Most HCAs are detected during a physical examination without clinical symptoms, and some patients may present with symptoms such as abdominal pain, abdominal distension, and abdominal masse. Serum liver function tests can show increased alkaline phosphatase (ALP) and γ- glutamyl transferase (GT), whereas α-Fetoprofein (AFP) levels are normal. The definitive diagnosis relies mainly on histopathological examination. Because HCAs can rupture and bleed and become malignant. Early surgical treatment is recommended after detection.